Macroscopy predicts tumor progression in gastric cancer: A retrospective patho-historical analysis based on Napoleon Bonaparte's autopsy report. Issue 11 (November 2016) - Dawson, Heather; Novotny, Alexander; Becker, Karen; Reim, Daniel; Langer, Rupert; Gullo, Irene; Svrcek, Magali; Niess, Jan H.; Tutuian, Radu; Truninger, Kaspar; Diamantis, Ioannis; Blank, Annika; et al.
Abstract: Background: The cause of Napoleon Bonaparte's death remains controversial. Originally suggested to be gastric cancer, whether this was truly neoplastic or a benign lesion has been recently debated. Aims: To interpret findings of original autopsy reports in light of the current knowledge of gastric cancer and to highlight the significance of accurate macroscopy in modern-day medicine. Methods: Using original autopsy documents, endoscopic images and data from current literature, Napoleon's gastric situation was reconstructed. In a multicenter collection of 2071 gastric cancer specimens, the relationship between tumor size and features of tumor progression was assessed. Results: Greater tumor size was associated with advanced pT, nodal metastases and Borrmann types 3–4 ( p < 0.001). The best cut-off for predicting pT3-4 tumors was 6.5 cm (AUC 0.8; OR 1.397, 95% CI 1.35–1.446), and 6 cm for lymph node metastases (AUC 0.775; OR 1.389, 95% CI 1.338–1.442). The 6 cm cut-off of had a positive predictive value of 0.820 for nodal metastases and a negative predictive value of 0.880 for distant metastases. Conclusion: This analysis combines Napoleon's autopsy with present-day knowledge to support gastric cancer as his terminal illness and emphasizes the role of macroscopy, which may provide valuable information on gastric cancer progression and aid patient management.